2021
DOI: 10.3390/microorganisms9081788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Diet CP, NDF, EE, and Starch on the Rumen Bacteria Community and Function in Dairy Cattle

Abstract: To understand the effects of diet and age on the rumen bacterial community and function, forty-eight dairy cattle at 1.5 (M1.5), 6 (M6), 9 (M9), 18 (M18), 23 (M23), and 27 (M27) months old were selected. Rumen fermentation profile, enzyme activity, and bacteria community in rumen fluid were measured. The acetate to propionate ratio (A/P) at M9, M18, and M23 was higher than other ages, and M6 was the lowest (p < 0.05). The total volatile fatty acid (TVFA) at M23 and M27 was higher than at other ages (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In terms of relative abundance, the propionate-producing bacteria Succinivibrionaceae UCG-002 is an crucial member of the family Succinivibrionaceae, which compete with methanogens to produce succinate and propionate instead of methane using hydrogen as a substrate, thereby reducing methane emissions and improving feed energy utilization ( Pope et al, 2011 ; Danielsson et al, 2017 ). Previous researches found that the Succinivibrionaceae_UCG-002 has a positive correlation with rumen TVFA and acetate production in dairy cattle ( Hao et al, 2021 ) or feed efficiency in sheep ( Zhang et al, 2021 ). In our trial, the relative abundance of Succinivibrionaceae_UCG-002 in the SeHLan added groups was significantly higher than control group, and the LSE and MSE groups had the highest abundance of Succinivibrionaceae_UCG-002 , while the CG and HSE groups had the lowest abundance of Succinivibrionaceae_UCG-002 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of relative abundance, the propionate-producing bacteria Succinivibrionaceae UCG-002 is an crucial member of the family Succinivibrionaceae, which compete with methanogens to produce succinate and propionate instead of methane using hydrogen as a substrate, thereby reducing methane emissions and improving feed energy utilization ( Pope et al, 2011 ; Danielsson et al, 2017 ). Previous researches found that the Succinivibrionaceae_UCG-002 has a positive correlation with rumen TVFA and acetate production in dairy cattle ( Hao et al, 2021 ) or feed efficiency in sheep ( Zhang et al, 2021 ). In our trial, the relative abundance of Succinivibrionaceae_UCG-002 in the SeHLan added groups was significantly higher than control group, and the LSE and MSE groups had the highest abundance of Succinivibrionaceae_UCG-002 , while the CG and HSE groups had the lowest abundance of Succinivibrionaceae_UCG-002 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Pseudobutyrivibrio was correlated positively with the molar proportion of acetate and negatively with total VFAs concentration, which is in accordance with the reports that this bacterium is cellulotytic ( Poonko et al, 2015 ). Therefore, it was correlated positively with dietary fiber content and negatively with dietary protein and starch ( Hao et al, 2021 ). The reason for the negative correlation of Prevotella , Prevotellaceae_UCG-001 , and Prevotellaceae_UCG-003 with total VFAs concentration is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that Candidatus_Saccharimonas was positively correlated with ruminal propionate concentrations in dairy cows [ 30 ]. Saccharofermentans belongs to the Bacteroidetes phylum and participates in hemicellulose, pectin, arabinogalactan, starch, fructan, and chitin degradation [ 31 ]. In addition, this study showed that Erysipelotrichaceae UCG-009 was positively associated with the production of butyrate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%